2004
DOI: 10.1111/j.1600-0897.2004.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Danger‐dependent Cytokine‐boosted Spontaneous Abortion in the CBA × DBA/2 Mouse Model. I. Synergistic Effect of LPS and (TNF‐α + IFN‐γ) on Pregnancy Loss

Abstract: High endogenous rates of abortion in the CBA x DBA/2 model may be explained by exposure to LPS at the time of mating. Increased rates of loss triggered by cytokines later in pregnancy may depend on increased absorption of LPS from intestinal flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 42 publications
1
61
0
1
Order By: Relevance
“…The Th1 cytokines over-expression in the uterus, such as IFN-and TNF-, affects the precious immunological response at the feto-maternal interface at embryo implantation stage. Meanwhile, the balance of Th1/Th2 was altered towards to Th1 predominant which is detrimental to pregnancy and induced embryo loss (Clark et al, 2004). The serum TNF-¡ IL-1 ¡ IL-6 levels and the receptor of induced by LPS were increased; however, there was no immunological response in fetal tissue, because LPS may not pass through the placentas and mainly affects the maternal immunologic tolerance (Rounioja et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The Th1 cytokines over-expression in the uterus, such as IFN-and TNF-, affects the precious immunological response at the feto-maternal interface at embryo implantation stage. Meanwhile, the balance of Th1/Th2 was altered towards to Th1 predominant which is detrimental to pregnancy and induced embryo loss (Clark et al, 2004). The serum TNF-¡ IL-1 ¡ IL-6 levels and the receptor of induced by LPS were increased; however, there was no immunological response in fetal tissue, because LPS may not pass through the placentas and mainly affects the maternal immunologic tolerance (Rounioja et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] DBA/2-mated CBA/J mice (CBA/J ϫ DBA/2) are a wellstudied model of pregnancy loss that shares features with human recurrent miscarriage. 7,8 Embryos derived from mating CBA/J females with DBA/2 males showed an increased frequency of resorption compared with control matings (CBA/J ϫ BALB/c) and surviving fetuses show consistent and significant growth restriction.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Other authors showed that high frequency of abortion in the CBA/J ϫ DBA/2 model may be explained by exposure to bacterial lipopolysaccharides (LPSs) at the time of mating 8,11,12 or increased absorption of LPS from intestinal flora. 7,[11][12][13] A variety of inflammatory stimuli, including bacterial cell products and components of the complement system, are known to promote the expression of tissue factor (TF) on the surface of endothelial cells, monocytes, and neutrophils. [14][15][16] In view of previous studies showing that aberrant TF expression may be responsible for thrombosis, we considered the possibility that increased TF expression induces pathological activation of the coagulation pathway, placental failure, fetal death, and growth restriction in this model of spontaneous abortion.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of fewer offspring is readily observed when these mice are mated, and the resorption of fetuses can be examined by killing the pregnant animals. These studies have provided important data with regard to miscarriage and its causes, including the interesting role of bacterial lipopolysaccharide (13). However, the tools to predict which fetuses will be resorbed and which will survive have yet to be exploited in this model.…”
Section: Discussionmentioning
confidence: 99%